120k views
3 votes
Can someone help me with this please

Can someone help me with this please-example-1

2 Answers

5 votes

Answer:


(d^(2)y)/(dx^(2)) = 180x.(x^(3) +8)^(4)

Explanation:

This question requires use of the chain rule:


y = (x^(3) + 8)^(6)

Let:


u = x^(3) + 8

Then:


y = u^(6)

And:


(dy)/(dx) = (dy)/(du). (du)/(dx)\\\\(d^(2)y)/(dx^(2) ) = (d^(2)y)/(du^(2)). (d^(2)u)/(dx^(2))\\\\(dy)/(du) = 6u^(5)\\\\(d^(2)y)/(du^(2)) = 30u^(4)\\\\(du)/(dx) = 3x^(2)\\\\(d^(2)u)/(dx^(2)) = 6x

So:


(dy)/(dx) = 6u^(5).3x^(2)\\\\(dy)/(dx) = 18u^(5)x^(2)\\\\

And:


(d^(2)y)/(dx^(2)) = 30u^(4).6x\\\\(d^(2)y)/(dx^(2)) = 180u^(4)x

Finally, substitute u for its equivalent expression in x:


(d^(2)y)/(dx^(2)) = 180x.(x^(3) +8)^(4)

User Davin Tryon
by
5.9k points
6 votes

Answer:

y'' = 18x(x³ + 8)⁴(17x³ + 16)

General Formulas and Concepts:

Calculus

Derivative Notation dy/dx

Derivative of a constant is 0.

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Chain Rule:
(d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Product Rule:
(d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Explanation:

Step 1: Define

y = (x³ + 8)⁶

Step 2: Find 1st Derivative (dy/dx)

  1. Chain Rule [Basic Power]: y' = 6(x³ + 8)⁶⁻¹ · (3x³⁻¹ + 0)
  2. Simplify: y' = 6(x³ + 8)⁵ · 3x²
  3. Multiply: y' = 18x²(x³ + 8)⁵

Step 3: Find 2nd Derivative (d²y/dx²)

  1. Product Rule [Chain/Basic Power]: y'' = 2 · 18x²⁻¹ · (x³ + 8)⁵ + 18x² · 5(x³ + 8)⁵⁻¹ · (3x³⁻¹ + 0)
  2. Simplify: y'' = 36x(x³ + 8)⁵ + 90x²(x³ + 8)⁴ · 3x²
  3. Multiply: y'' = 36x(x³ + 8)⁵ + 270x⁴(x³ + 8)⁴
  4. Factor: y'' = 6x(x³ + 8)⁴[6(x³ + 8) + 45x³]
  5. Distribute: y'' = 6x(x³ + 8)⁴[6x³ + 48 + 45x³]
  6. Combine like terms: y'' = 6x(x³ + 8)⁴[51x³ + 48]
  7. Factor: y'' = 6x(x³ + 8)⁴ · 3(17x³ + 16)
  8. Multiply: y'' = 18x(x³ + 8)⁴(17x³ + 16)
User Rahul Bohare
by
5.9k points